2021
DOI: 10.34117/bjdv7n6-386
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento alimentar em tempos de pandemia por Covid-19 / Eating behavior in times by Covid-19

Abstract: Em decorrência da pandemia por covid-19 foi realizada uma pesquisa através do envio de um questionário eletrônico divulgado nas redes sociais no período de 30 dias e dividida em duas fases: Fase 1 de 01 a 30 de julho de 2020 e Fase 2 do dia 11 de janeiro a 11 de fevereiro de 2021 com objetivo de compreender a influência do distanciamento social no comportamento alimentar e os mecanismos compensatórios adaptativos desenvolvidos em situação de estresse. Em ambas as fases obtiveram prevalência das respostas pelo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
2
2
0
12
Order By: Relevance
“…At the same time, at T2, that number dropped to 45.5%, showing an increase in the number of people who were partially complying with or were not adopting any type of social distancing ( p < 0.001). A similar finding was observed in a study carried out with Brazilian adults, which showed an 11.1% reduction in participant compliance with the strictest physical/social distancing measures from the first phase (July 2020) to the second (February 2021) [ 28 ]. Regarding the occupational situation, the present study showed a reduction in the number of people working remotely and an increase in partially remote or entirely in-person work ( p < 0.001).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At the same time, at T2, that number dropped to 45.5%, showing an increase in the number of people who were partially complying with or were not adopting any type of social distancing ( p < 0.001). A similar finding was observed in a study carried out with Brazilian adults, which showed an 11.1% reduction in participant compliance with the strictest physical/social distancing measures from the first phase (July 2020) to the second (February 2021) [ 28 ]. Regarding the occupational situation, the present study showed a reduction in the number of people working remotely and an increase in partially remote or entirely in-person work ( p < 0.001).…”
Section: Discussionsupporting
confidence: 84%
“…In Brazil, studies have already demonstrated changes in the eating habits of adolescents [ 10 ], worsening quality of life for adults [ 15 ], worsening eating patterns in underdeveloped regions of the country [ 23 ], changes in the self-perception of the health of adult individuals [ 24 ], and high prevalence of psychiatric disorders and binge eating [ 25 ]. However, most studies carried out in Brazil and around the world showed a perspective on the changes observed at the beginning of the implementation of the lock-down decrees and distancing/isolation measures—more or less restricted according to each region—and so far, few have presented data collected at two or more moments, covering the periods of the flexibility of preventive measures [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This deterioration in the quality of food was also found in other studies and was related to the increase in the consumption of processed foods and the purchase of fast food meals, linked to the so-called “harmful actions” such as the absence of physical activity, cigarette use, and alcoholic beverages ( 20 , 21 ).…”
Section: Resultssupporting
confidence: 74%
“…Diante da nova realidade vivida frente à pandemia do Coronavírus, pessoas do mundo todo passaram a viver em isolamento social, o que trouxe novos hábitos de vida e consequentemente, alimentares. Estudos demonstram maiores números de preparação de refeições no ambiente familiar e em contraposição, aumento também no consumo de comidas ultra processadas, fast foods e bebidas alcoólicas (Aro et al, 2021;Maynard et al, 2020). Além disso, o novo estilo de vida adaptado ao isolamento social acarretou em alterações psicológicas relacionadas a estresse e ansiedade, com influência direta nas escolhas alimentares e consequentemente, na ingestão de nutrientes (Aro et al, 2021).…”
Section: Introductionunclassified